Two new species of the genus Halaphanolaimus De Man, 1876 (Nematoda: Leptolaimidae) from Can Gio mangrove forest, Vietnam - Gagarin, Vladimir G.; Thanh, Nguyen Vu (Academia Journal of Biology, 2014)
New brackish water nematode species Halaphanolaimus cangionensis sp.nov, and Halaphanolaimus rivalis sp.nov collected from Cangio mangrove forest, Hochiminh city of Vietnam are described. Halaphanolaimus cangionensis sp.nov is characterized by the absence of somatic and cervical setae, comparatively slender tail, presence of caudal apophysis of the gubernaculum and comparatively short spicules. New species Halaphanolaimus cangionensis sp.nov resembles to Halaphanolaimus harpaga Boucher, Bovee, 1972 and Halaphanolaimus luridus (Timm, 1963) but differs from H. harpaga by the absence of somatic and cervical setae, more anterior position of vulva, another structure of gubernaculums and other arrangement of precloacal supplements. The new species differs from H. luridus by the more slender tail, longer stoma, another structure of gubernaculums and shorter spicules. Halaphanolaimus rivalis sp.nov is characterized by the presence of somatic and servical setae, long spicules and pre-equatorial vulva. New species Halaphanolaimus rivalis sp.nov, resembles to Halaphanolaimus luridus (Timm, 1963) and L. lorenzeni Boucher, Bovee, 1972 but H. rivalis sp.n. differs from H. luridus by the presence of somatic and cervical setae, more wide labial region, longer stoma, shorter spicules. H. rivalis sp.n. differs from H. lorenzeni by the thicker body, longer stoma and longer spicules. Key to six valid species of the genus Halaphanolaimus are given.